2004
DOI: 10.1021/ja031698u
|View full text |Cite
|
Sign up to set email alerts
|

Glycodendriproteins:  A Synthetic Glycoprotein Mimic Enzyme with Branched Sugar-Display Potently Inhibits Bacterial Aggregation

Abstract: The continuing ability of bacteria to resist current antibiotic treatments highlights the need for alternative strategies for inhibiting their pathogenicity. Bacterial attachment is a major factor in infectivity and virulence. This key binding phase of bacteria to any potential host is mediated by adhesin proteins and so these present an attractive therapeutic target for antiinfective blocking strategies. However, the natural ligands to adhesins are large, typically complex molecules that are difficult to mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 33 publications
(60 reference statements)
1
78
0
Order By: Relevance
“…[30][31][32][33][34] Microtiter plates are coated with a reference ligand (often a (neo)glycoprotein or polysaccharide) and IC 50 values for inhibition of the binding of an enzyme-labeled lectin to the immobilized reference ligand (the matrix) by the soluble ligands to be tested are determined. The advantage of ELLA compared to solid-phase binding assays such as surface plasmon resonance (SPR) 35 is that both, lectin and ligand are in solution.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] Microtiter plates are coated with a reference ligand (often a (neo)glycoprotein or polysaccharide) and IC 50 values for inhibition of the binding of an enzyme-labeled lectin to the immobilized reference ligand (the matrix) by the soluble ligands to be tested are determined. The advantage of ELLA compared to solid-phase binding assays such as surface plasmon resonance (SPR) 35 is that both, lectin and ligand are in solution.…”
Section: Introductionmentioning
confidence: 99%
“…95 Davis' group showed that the attachment of a carbohydrate based dendron onto a glycoprotein protease facilitated the anchoring of the hybrid construct onto bacterial cell surfaces. 96 Subsequent cleavage of the membrane proteins by the glycoprotein protease inhibited the infectivity of the bacteria, Actinomyces naeslundii, with an IC 50 = 20 nM. 96 Through this approach, dendronized proteins emerged as a novel class of hybrid materials exhibiting synergistic biological properties while simultaneously maintaining molecular definition.…”
Section: Protein-dendron Core-shell Architecturementioning
confidence: 99%
“…[30] Dendrimers show great promise for applications in therapeutic processes since they can adopt a protein-like structure and thus mimic the branched carbohydrates of natural glycoproteins. [31] Such glycosylation techniques, performed by step growth condensation strategies, may help to overcome problems associated with heterogenous glycoproteins synthesis. [32] A variety of scaffolds are available, e.g., commercial polyamidoamine PAMAM, which can be used to synthesize multivalent ligands with carbohydrate density increasing with the generation.…”
Section: Synthesis Of Carbohydrate-polymer Hybridsmentioning
confidence: 99%